Biomimetic chemical sensors using bioengineered olfactory and taste cells - Du, Liping (Landes Bioscience, 2014)
Biological olfactory and taste systems are natural chemical sensing systems with unique performances for the detection of environmental chemical signals. With the advances in olfactory and taste transduction mechanisms, biomimetic chemical sensors have achieved significant progress due to their promising prospects and potential applications. Biomimetic chemical sensors exploit the unique capability of biological functional components for chemical sensing, which are often sourced from sensing units of biological olfactory or taste systems at the tissue level, cellular level, or molecular level. Specifically, at the cellular level, there are mainly two categories of cells have been employed for the development of biomimetic chemical sensors, which are natural cells and bioengineered cells, respectively. Natural cells are directly isolated from biological olfactory and taste systems, which are convenient to achieve. However, natural cells often suffer from the undefined sensing properties and limited amount of identical cells. On the other hand, bioengineered cells have shown decisive advantages to be applied in the development of biomimetic chemical sensors due to the powerful biotechnology for the reconstruction of the cell sensing properties. Here, we briefly summarized the most recent advances of biomimetic chemical sensors using bioengineered olfactory and taste cells. The development challenges and future trends are discussed as well.